Risk of Hepatotoxicity in Leflunomide Vs Methotrexate in Treatment of Rheumatoid Arthritis - Saima Riaz, Tafazzul E Haque Mahmud, Aflak Rasheed, Adnan Wajih Akhtar, Asad Javed, Umair Javaid, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the hepatotoxicity in Leflunomide vs Methotrexate in rheumatoid arthritis patients. Study design: Cross sectional study. Place and duration of study: Study was conducted from Jun 2021 to Mar 2022 at Department of Rheumatology and immunology Sheikh Zayed Hospital Lahore. Methodology: Inclusion criteria were any patient aged between 18-70 years males and females. Patients who were diagnosed with RA according to ACR criteria 2010. Exclusion criteria were pregnancy, Known case of hepatitis B or C, patients having known hypersensitivity to DMARDS. Group A (MTX) of 150 patients received 20 mg/week of MTX and Group B (LEF) of 150 patients received 20mg/day of LEF. The collected data was analyzed on (SPSS) version 24.0. Results: 40 patients were excluded from study. Mean age of patients in Group A (MTX) was 52.73±9.34 years and in Group B (LEF) it was 51.15 + 9.79 years. 44 patients (33.8%) of group A which were given MTX developed GI symptoms while 22 patients (16.9%) of group B who were given LEF developed GI symptoms. Similarly hepatotoxicity was seen in 15 patients (11.5%) of MTX group while 27 patients (20.8%) of LEF group developed hepatotoxicity which was statistically significant (p = 0.04). 5 patients (3.8%) of LEF developed liver fibrosis. Conclusion: We conclude that most LEF with rapid onset of action is quicker in reducing symptoms of RA patients and is associated with high degree of hepatotoxicity with low liver fibrosis when compared with MTX.